Hybrid mode-locked 2 μm fiber laser with sub-megahertz repetition rate - Do Lim, Sun; Gene, Jinhwa; Kim, Seung Kwan; Yeom, Dong Il (Optics InfoBase Conference Papers, 2018)
We demonstrated a high pulse energy, passively mode-locked thulium-doped fiber (TDF) laser with a repetition rate of 427 kHz, the lowest repetition rate at 2 μm to the best of our knowledge. Two stages of TDF amplifier is applied to obtain sufficient gain over high attenuation of 485 m long oscillator. The self-starting of passively mode-locking is realized by using a nonlinear polarization rotation technique in association with an in-line graphene saturable absorber. The mode-locked TDF laser delivers stable femtosecond pulses with a pulse energy of 54 nJ.
Keywords: High pulse energy; Hybrid mode; Low repetition rate; Mode-locked; Passively mode-locked; Passively mode-locking; Repetition rate; Self-starting; Thulium doped fiber amplifiers; Thulium-doped fibers